Combinatorial Peptide Library Protocols - Cabilly, Shmuel.; Cabilly, Shmuel. (Methods in Molecular Biology, 1998)
Shmuel Cabilly presents in Combinatorial Peptide Library Protocols a collection of new and unique techniques for the construction and use of peptide libraries. These powerful methods-often detailed here by their pioneers-include protocols for the chemical synthesis of peptide libraries, for constructing peptide libraries that are displayed on the surface of filamentous phage or bacteria, and for the rapid screening of these libraries for molecules with biospecific properties. Additional methods permit identifying specific enzyme substrates, investigating the recognition spectra of various binding proteins, epitope mapping, and identifying mimotopes. Combinatorial Peptide Library Protocols offers novice and experienced investigators alike the ability to select molecules from a randomized pool having specific biological activities. Its state-of-the-art techniques, combined with clear step-by-step instructions, make this book an essential tool in the selection of peptides suitable for drug development.